Post-synthetically modified porous covalent framework (PCF) for high proton conduction - Samanta, Partha; Desai, Aamod; Anothumakkool, Bihag; Shirolkar, Mandar; Karmakar, Avishek; Kurungot, Sreekumar; Ghosh, Sujit (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Porous Covalent Framework; Post-synthetic Modification; proton conduction

Sulfonic acid loaded self-standing covalent organic membrane for proton conduction - Sasmal, Himadri Sekhar; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: COF; Membrane; proton conduction

Two-in-one: inherent anhydrous and water-assisted high proton conduction in a 3D metal-organic framework - Nagarkar, Sanjog S.; Unni, SreeKuttan M.; Sharma, Amitosh; Kurungot, Sreekumar; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2014)
The development of solid-state proton-conducting materials with high conductivity that operate under both anhydrous and humidified conditions is currently of great interest in fuel-cell technology. A 3Dmetal-organic framework (MOF) with acid-base pairs in its coordination space that efficiently conducts protons under both anhydrous and humid conditions has now been developed. The anhydrous proton conductivity for this MOF is among the highest values that have been reported for MOF materials, whereas its water-assisted proton conductivity is comparable to that of the organic polymer Nafion, which is currently used for practical applications. Unlike other MOFs, which conduct protons either under anhydrous or humid conditions, this compound should represent a considerable advance in the development of efficient solid-state proton-conducting materials that work under both anhydrous and humid conditions.
Keywords: conducting materials; fuel cells; metal-organic frameworks; porous materials; proton conduction

Lithium-assisted proton conduction at 150 degrees C in a microporous triazine-phenol polymer - Nandi, Shyamapada; Dhavale, Vishal M.; Shalini, Sorout; Werner-Zwanziger, Ulrike; Singh, Harpreet; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Materials Interfaces, 2015)
Keywords: conduction; hydrophobic polar frameworks; lithiated polymers; proton conduction; triazine-phenol polymers

Hydrogen-bonded organic frameworks (HOFs): a new class of porous crystalline proton-conducting materials - Karmakar, Avishek; Illathvalappil, Rajith; Anothumakkool, Bihag; Sen, Arunabha; Samanta, Partha; Desai, Aamod V.; Kurungot, Sreekumar; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2016)
Two porous hydrogen-bonded organic frameworks (HOFs) based on arene sulfonates and guanidinium ions are reported. As a result of the presence of ionic backbones appended with protonic source, the compounds exhibit ultra-high proton conduction values (sigma) 0.75x 10(-2)Scm(-1) and 1.8x10(-2)Scm(-1) under humidified conditions. Also, they have very low activation energy values and the highest proton conductivity at ambient conditions (low humidity and at moderate temperature) among porous crystalline materials, such as metal-organic frameworks (MOFs) and covalent organic frameworks (COFs). These values are not only comparable to the conventionally used proton exchange membranes, such as Nafion used in fuel cell technologies, but is also the highest value reported in organic-based porous architectures. Notably, this report inaugurates the usage of crystalline hydrogen-bonded porous organic frameworks as solid-state proton conducting materials.
Keywords: guanidinium; hydrogen-bonded organic frameworks; porous crystalline frameworks; proton conduction; sulfonates

Proton conductivity in a copper(II) bipyridine glycoluril complex: the synergistic role of coordinated water and hydrogen-bonded networks - Khatavkar, Medhavi D.; Panday, Rishukumar; Singh, Mayank U.; Kurungot, Sreekumar; Kumbhar, Avinash S. (Inorganica Chimica Acta, 2026)
A dinuclear complex of copper(II) and bipyridine glycoluril (BPG) ligand is synthesized, characterized, and structurally examined by single-crystal X-ray diffraction. The complex [Cu2(BPG)2(NO3)2(H2O)4](NO3)2 center dot 5H2O (complex (1)) further forms a supramolecular network sustained by H-bonds between NH/C=O of BPG, coordinated/free water molecules, and nitrate anions. The complex exhibits a proton conductivity of 5.99 x 10_ 3 S center dot cm_ 1 at 90 degrees C and 95 % relative humidity (RH) with activation energy value Ea 0.35 eV, suggesting the Grotthuss proton transport mechanism. This value is consistent with those reported for proton-conducting systems in which coordinated water molecules play a critical role in facilitating efficient proton hopping across hydrogen-bonded networks.
Keywords: Coordinated water; Copper(II) complex; H -bonding; proton conduction; Supramolecular networks